Dopant-Free Hole-Transport Materials with Germanium Compounds Bearing Pseudohalide and Chalcogenide Moieties for Perovskite Solar Cells - Soto Montero, Tatiana (2020)
Hole-transport materials (HTMs) are key electronic components for the functioning of perovskite solar cells (PSCs) as they extract the photogenerated holes from the perovskite to be transported subsequently to the back electrode while minimizing the loss from electron recombination. Herein, we report the synthesis and characterization of novel germanium-based compounds with [{HC(CMeNAr)2}GeNCS] (2), [{HC(CMeNAr)2}Ge(S)NCS] (3), and [{HC(CMeNAr)2}Ge(Se)NCS] (4) compositions, with Ar = 2,6-iPr2C6H3 and the photovoltaic performance of 3 and 4 that is the same as for HTM in PSC. All compounds displayed excellent thermal properties and an appropriate alignment of energy levels for the perovskite with maximum optical absorption in the near-UV region. As revealed by space-charge limited-current (SCLC) measurements, compounds 3 and 4 have competing hole mobilities of about 1.37 × 10–4 and 4.88 × 10–4 cm2 V–1 s–1, respectively. Upon assessing PSC devices using 3 and 4 with triple-cation perovskite absorber Cs0.05(MA0.17FA0.83)0.95Pb(I0.83Br0.17)3, the power conversion efficiencies (PCEs) were about 13.03 and 9.23%, respectively, both without doping and additives, and were compared with benchmark HTM spiro-OMeTAD (2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine)-9,9′-spirobifluorene). Quantum chemical calculations with DFT showed that the optoelectronic properties are strongly influenced by the combined contributions of the germanium atom, the pseudohalide moiety (NCS–), and chalcogenides (S2– or Se2–). Fine tuning the electronic properties of germanium is thus a good strategy for the targeted synthesis of potential conducting molecules in PSCs.